Membrane vesicles from Pseudomonas aeruginosa activate the noncanonical inflammasome through caspase‐5 in human monocytes. Issue 10 (14th August 2018) - Bitto, Natalie J; Baker, Paul J; Dowling, Jennifer K; Wray‐McCann, Georgie; De Paoli, Amanda; Tran, Le Son; Leung, Pak Ling; Stacey, Katryn J; Mansell, Ashley; Masters, Seth L; Ferrero, Richard L
Abstract: Outer membrane vesicles (OMVs) are constitutively produced by Gram‐negative bacteria both in vivo and in vitro . These lipid‐bound structures carry a range of immunogenic components derived from the parent cell, which are transported into host target cells and activate the innate immune system. Recent advances in the field have shed light on some of the multifaceted roles of OMVs in host–pathogen interactions. In this study, we investigated the ability of OMVs from two clinically important pathogens, Pseudomonas aeruginosa and Helicobacter pylori, to activate canonical and noncanonical inflammasomes. P. aeruginosa OMVs induced inflammasome activation in mouse macrophages, as evidenced by "speck" formation, as well as the cleavage and secretion of interleukin‐1β and caspase‐1. These responses were independent of AIM2 and NLRC4 canonical inflammasomes, but dependent on the noncanonical caspase‐11 pathway. Moreover, P. aeruginosa OMVs alone were able to activate the inflammasome in a TLR‐dependent manner, without requiring an exogenous priming signal. In contrast, H. pylori OMVs were not able to induce inflammasome activation in macrophages. Using CRISPR/Cas9 knockout THP‐1 cells lacking the human caspase‐11 homologs, caspase‐4 and ‐5, we demonstrated that caspase‐5 but not caspase‐4 is required for inflammasome activation by P. aeruginosa OMVs in human monocytes. In contrast, free P. aeruginosa lipopolysaccharide (LPS) transfected into cells induced inflammasome responses via caspase‐4. This suggests that caspase‐4 and caspase‐5 differentially recognize LPS depending on its physical form or route of delivery into the cell. These findings have relevance to Gram‐negative infections in humans and the use of OMVs as novel vaccines. Abstract : Pseudomonas aeruginosa outer membrane vesicles (OMVs) induce inflammasome formation in mouse macrophages via the noncanonical caspase‐11 pathway. In human monocytes, P. aeruginosa OMVs selectively induce inflammasome activation via the caspase‐11 homolog, caspase‐5. In contrast, caspase‐4 is required for inflammasome activation in response to P. aeruginos a lipopolysaccharide transfected into cells.